Importance of Theories to the Processes of Educational Policymaking and Planning: A Case Study on the Recent Educational Developments in Ghana - Donkoh, Ruth; Lee, Wing O.; Donkor, Josephine; Akotey, Martin K.; Twerefoo, Portia Oware; Boateng, Solomon A (International Journal of Educational Development in Africa)
Although theories and processes of educational policymaking and planning are relevant in educational development, an assessment of them in Ghana revealed that they are boycotted; hence, the inability of educational developments to achieve their objectives. This article reports on a study that analysed the theories, and processes of educational policymaking and planning on the recent educational development in Ghana. From the findings, the article argues that the recognition of theories and approaches to policymaking and planning can help to bring sanity to the situation and overhaul Ghana’s educational system. This can be achieved by allowing educational stakeholders to do due diligence on their work in order to achieve their educational objectives.